03.08 High vitamin d levels may downregulate inflammation in behçet's disease patients. (1st March 2017) - Adeeb, Fahd; Khan, Maria Usman; Stack, Austin; Fraser, Alexander D.
Abstract : Background: Vitamin D has been shown to be directly or indirectly involved in the regulation of proliferation, differentiation, and function of immune cells. Many studies have revealed higher levels of Vitamin D deficiency among patients with autoimmune diseases compared to controls. Aim: Aim of the study was to evaluate the serum 25-hydroxyvitamin D (25(OH)D) levels in Behçet's disease (BD) patients in the midwest region of Ireland, and to correlate with its disease activity. Methods: All BD patients attending our rheumatology service and satisfying the ISGBD/ICBD criteria were included in the study and compared in a 1:5 ratio with samples taken from controls matched for age, gender- and the month of the year. Exclusion criteria included other rheumatological or bone/skeletal diseases, a history of chronic kidney disease or other chronic systemic diseases, malignancies, limited physical activity, and if on vitamin D supplementation or medications that could have affected vitamin D metabolism including calcium supplements, cytotoxic drugs, anticonvulsants, bisphosphonates and thyroxine but not glucocorticoids and disease-modifying anti-rheumatic drugs. The total serum 25(OH)D was measured by using competitive chemiluminescence immunoassays (DiaSorin, Dietzenbach, Germany). Levels<20 ng/ml were defined as deficient, between 20–40 ng/ml as insufficient. Results: 19 Caucasian BD patients were included in the study (5 male, 14 female, median age of 37.5 years (interquartile range (IQR), 24.3–51.2 years). The median 25(OH)D of BD patients and controls were 45 ng/ml (IQR, 33–65 ng/ml) and 22 ng/ml (IQR, 15–31 ng/ml) respectively. The median 25(OH)D was relatively lower in active BD patients in comparison to inactive patients: 35 ng/ml (IQR, 22.75–47.25 ng/ml) compared to 50 ng/ml (IQR, 35–67 ng/ml). Overall, none of the patients had Vit D deficiency, however 6 patients had Vit D insufficiency. Conclusion: In contrast to many previous studies in other BD cohorts and other autoimmune diseases our study suggests the mean 25(OH)D levels was significantly higher in this BD group. In patients with active disease however serum levels were relatively low compared to the inactive group which is in concordance with the literature. Our findings suggest vitamin D may be a potential suppressor of inflammation in BD, however larger studies are needed to support this thesis and to conclusively understand its role in the inflammatory pathway.